Coaching clinik meningkatkan kebugaran jasmani pada lanjut usia melalui aktivitas fisik di Yakes Telkom Area 7 Kepulauan - Hasyim Hasyim; Imam Imam; Silatulrahmi Silatulrahmi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The purpose of community service is to improve the physical fitness of the elderly (retirees) telkom area 7 telecommunications islands through coaching clinic through physical activity (sports) using fitness equipment. The solutions offered are: Improve physical fitness related to health such as lung heart endurance and strength training in elderly Telkom yakes area 7 islands. Through this Community Service activity, the types of results produced are: 1). Applying partners to the use of physical fitness equipment related to health such as endurance of the heart of the lungs and strength training 2) Guiding retirees to Telkom Area 7 islands increases motivation and health benefits for the elderly (retirees) in training. Health-related physical fitness includes aspects of physiological functions that offer prevention against disease as a result of a sedentary lifestyle. This can be enhanced and / or maintained through regular physical activity programs and based on the principles of correct practice. The components of physical fitness related to health according to Wahjoedi (2000: 59) include, "Endurance of the heart of the lungs, endurance of muscles, muscle strength, flexibility and body composition". The elements of physical fitness related to health must be considered and sought in order to achieve a degree of total physical fitness (total fitness) Physical fitness needed by the elderly is health related fitness that is heart-lung fitness, muscle endurance, muscle strength, flexibility and body composition. To get good physical fitness, one must train all the basic components of physical fitness which consist of: heart-lung endurance, muscular endurance, muscle strength, body flexibility, blood circulation and breathing. Thus that the level of physical fitness is sufficient, so it is necessary to improve physical fitness related to health in physical activity clinic training participants such as the use of fitness equipment to get optimal results in the elderly of Telkom area 7 islands. Through the Community Partnership Program activities, the resulting output targets are 1) Proceedings at the UNM Makassar national seminar, 2) Media on line, 3) Partners are able to or improve physical fitness in the elderly (retirees) through physical activity.